Puanhayati Jawa Tengah Sebagai Media Aktualisasi Perempuan dan Pelestarian Budaya - Angga, Vicky Verry; Purwanti, Eni; Dieni, Novita Al Ihyak; Hayati, Endah Dwi (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
Puanhayati is an organization of women adherents of the Indigenous Faith (Kepercayaan Terhadap Tuhan YME) that serves as a platform for self-actualization and the advocacy of women's rights in social, cultural, and national spheres. Since its declaration in 2017, Puanhayati has expanded its network to the provincial and district/city levels, with Central Java being one of its most active regions. The organization runs programs focused on economic empowerment, education and regeneration of spiritual values, advocacy of constitutional rights, strengthening of identity and leadership, and the preservation of local culture. Through culture-based training such as batik-making, Puanhayati plays a role in both preserving cultural heritage and enhancing the capacity of women adherents. Its commitment to national unity and diversity makes Puanhayati not only a platform for rights advocacy but also an agent of cultural and spiritual preservation. Puanhayati has proven its strategic role in empowering women adherents toward a more inclusive and just society.